PESONA WISATA ALAM DAN WISATA BUATAN DI KECAMATAN BALIGE KABUPATEN TOBA - Sarah Betty Tiomsi Simamora (CV. Adiba Aisha Amira, 2025)
The development of tourist attractions within a region requires careful consideration of several key factors to ensure the preservation of its unique characteristics. This developmental process, aimed at enhancing community well-being, should also prioritize the conservation of both natural and human resources within the area. The allure of natural and artificial tourist attractions presents a viable option for visitors seeking cost-effective experiences. The synergy between natural and artificial elements creates a distinctive appeal. The availability of resources is a critical determinant of the successful revitalization of existing attractions. Human resources possessing a strong commitment to environmental protection and conservation are essential in providing solutions to fundamental challenges in a tourist destination. Concerted efforts to maintain and restore these attractions are deemed beneficial in augmenting the appeal of both natural and artificial tourist destinations.